Role of miRNA in non-invasive diagnosis of Endometriosis - A pilot study - T. Ramani Devi; Balamuthu Kadalmani; C. Anchana Devi (Al Ameen Medical College, 2022)
Background: The Background of the study is to find out whether a panel of miRNAs from the serum of patients could be used as a biomarker for non-invasive diagnosis of endometriosis. Objective: A panel of miRNA 125b, miRNA150-5p, miRNA 342-3p, miRNA 3613-5p and Let-7b were studied in both control group who are found to be non-endometriotic patients and in the study group proven to be endometriotic patients. The objective is to find out whether these miRNAs could be used as a biomarker for diagnosis of endometriosis. Methodology: This study was done at Ramakrishna Medical Centre LLP. Patients undergoing laparoscopy for infertility and pain having endometriosis served as the study group and non-endometriotic patients served as the control group. Being a pilot study, we have included only 25 patients in each group. Based on the previous studies, a panel of 5 miRNAs were analysed from the serum of the women. Fasting sample was collected, serum was separated and cryo- preserved. q-RT-PCR analysis of the miRNA was done as per the protocols by a scientific team and results were analysed. Statistical analysis was done by generation of AUC. Results: miRNA 125b, miRNA 150-5p, miRNA 342-3p, miRNA 3613-5p and Let-7b were studied in both control and study group. There was up regulation of miRNA125b and miRNA342-3p and down regulation of Let-7b with the significant p value of <0.001. Conclusion: This pilot study shows that the panel of these miRNAs in peripheral circulating serum could be used as a non-invasive diagnostic marker for endometriosis.